Aprendizaje autorregulado en los estudiantes de décimo grado según el género en la Institución Educativa Juan José Rondón (2020)
This study sought to describe self-regulated learning in tenth grade students at the Juan José Rondón Educational Institution, through its motivational components and learning strategies based on the socio-cognitive theory of self-regulated learning. Through the application of the Motivation Questionnaire and Learning Strategies (CMEA), to a participating population of 27 schoolchildren. The type of research selected was quantitative, descriptive, non-experimental, cross-sectional. The results showed that tenth grade students have a motivational profile that is characterized by reasons oriented to external rewards, and to their own effort. On the other hand, the profile of use of learning strategies, the tenth-grade students execute their academic duties, mainly with deep elaboration strategies, critical thinking and the search for help. However, the same students use fewer repetition and effort regulation strategies. Also, differences by gender in favor of males were found in most of the different CMEA subscales.